Hyperbaric air mobilizes stem cells in humans; a new perspective on the hormetic dose curve - MacLaughlin, Kent J.; Barton, Gregory P.; Braun, Rudolf K.; MacLaughlin, Julia E.; Lamers, Jacob J.; Marcou, Matthew D.; Eldridge, Marlowe W. (Frontiers in Neurology, 2023)
Introduction Hyperbaric air (HBA) was first used pharmaceutically in 1662 to treat lung disease. Extensive use in Europe and North America followed throughout the 19th century to treat pulmonary and neurological disorders. HBA reached its zenith in the early 20th century when cyanotic, moribund “Spanish flu pandemic” patients turned normal color and regained consciousness within minutes after HBA treatment. Since that time the 78% Nitrogen fraction in HBA has been completely displaced by 100% oxygen to create the modern pharmaceutical hyperbaric oxygen therapy (HBOT), a powerful treatment that is FDA approved for multiple indications. Current belief purports oxygen as the active element mobilizing stem progenitor cells (SPCs) in HBOT, but hyperbaric air, which increases tensions of both oxygen and nitrogen, has been untested until now. In this study we test HBA for SPC mobilization, cytokine and chemokine expression, and complete blood count. Methods Ten 34–35-year-old healthy volunteers were exposed to 1.27ATA (4 psig/965 mmHg) room air for 90 min, M-F, for 10 exposures over 2-weeks. Venous blood samples were taken: (1) prior to the first exposure (served as the control for each subject), (2) directly after the first exposure (to measure the acute effect), (3) immediately prior to the ninth exposure (to measure the chronic effect), and (4) 3 days after the completion of tenth/final exposure (to assess durability). SPCs were gated by blinded scientists using Flow Cytometry. Results SPCs (CD45dim/CD34+/CD133-) were mobilized by nearly two-fold following 9 exposures (p = 0.02) increasing to three-fold 72-h post completion of the final (10th) exposure (p = 0.008) confirming durability. Discussion This research demonstrates that SPCs are mobilized, and cytokines are modulated by hyperbaric air. HBA likely is a therapeutic treatment. Previously published research using HBA placebos should be re-evaluated to reflect a dose treatment finding rather than finding a placebo effect. Our findings of SPC mobilization by HBA support further investigation into hyperbaric air as a pharmaceutical/therapy.